Extracellular ATP-Induced Alterations in Extracellular H+ Fluxes From Cultured Cortical and Hippocampal Astrocytes - Choi, Ji-in Vivien; Tchernookova, Boriana K.; Kumar, Wasan; Kiedrowski, Lech; Goeke, Calla; Guizzetti, Marina; Larson, John; Kreitzer, Matthew A.; Malchow, Robert Paul (Frontiers in Cellular Neuroscience, 2021)
Small alterations in the level of extracellular H+ can profoundly alter neuronal activity throughout the nervous system. In this study, self-referencing H+-selective microelectrodes were used to examine extracellular H+ fluxes from individual astrocytes. Activation of astrocytes cultured from mouse hippocampus and rat cortex with extracellular ATP produced a pronounced increase in extracellular H+ flux. The ATP-elicited increase in H+ flux appeared to be independent of bicarbonate transport, as ATP increased H+ flux regardless of whether the primary extracellular pH buffer was 26 mM bicarbonate or 1 mM HEPES, and persisted when atmospheric levels of CO2 were replaced by oxygen. Adenosine failed to elicit any change in extracellular H+ fluxes, and ATP-mediated increases in H+ flux were inhibited by the P2 inhibitors suramin and PPADS suggesting direct activation of ATP receptors. Extracellular ATP also induced an intracellular rise in calcium in cultured astrocytes, and ATP-induced rises in both calcium and H+ efflux were significantly attenuated when calcium re-loading into the endoplasmic reticulum was inhibited by thapsigargin. Replacement of extracellular sodium with choline did not significantly reduce the size of the ATP-induced increases in H+ flux, and the increases in H+ flux were not significantly affected by addition of EIPA, suggesting little involvement of Na+/H+ exchangers in ATP-elicited increases in H+ flux. Given the high sensitivity of voltage-sensitive calcium channels on neurons to small changes in levels of free H+, we hypothesize that the ATP-mediated extrusion of H+ from astrocytes may play a key role in regulating signaling at synapses within the nervous system.